German foreign policy towards Iran - Khatib-Shahidi, R; Shahidi, Rashid (1999)
﻿ The objective of this thesis is to show that after World War I, the National Bank of Persia emerged as an ideal accessory to Germany's desire to establish a foothold in Iran. It argues that the main motive behind Germany's involvement in the National Bank was to utilise the bank as a vehicle for extending German national interest into Iran. However, although Germany's main interest was to thereby gain economic influence in Iran, the National Bank provided Germany with a tool that furthered its desire for political participation and the establishing of authority within the spheres of interest of Britain and Russia. The objective of this thesis is not to establish a comprehensive and complete overview of German foreign policy toward Iran and its interactions with the National Bank of Persia. It aims rather at highlighting a number of events that are significant for an examination of Germany's policy toward Iran and its evolution up until the outset of World War II. In pursuit of this task, emphasis is given to the opinion expressed at the time, as reflected in German sources, rather than the historical reality behind those sources. German foreign policy towards Iran in the first half of the twentieth century can be divided into three distinct phases. The first phase, which was initiated before Word War I, collapsed as a consequence of the war and the Versailles Treaty, achieving little success. The second, more significant, phase began around 1924, and was marked by the creation of the National Bank of Persia in 1927, the appointment of the German national Lindenblatt as its director, the appointment of his compatriot Schniewind as financial advisor to the Persian government, the contracts granted to German companies and consortiums for the construction of the Trans Iranian Railway, the reestablishment of trade relations between Germany and Iran, and the wide-ranging flight concessions granted by the Iranian government to the German company Junkers. The third phase of Germany's involvement with Iran came about with the achievements that resulted from the trade agreements of 1935. From a German perspective after 1933 diplomacy started to replace the role of the National Bank, as the prime agent of Germany's relations with Iran. This phase lasted until the British-Russian invasion of Iran in 1941, and saw Germany lose almost its entire influence over the National Bank, while its influence over trade with Iran had progressively increased. Germany's foreign political success during the inter-war period resulted in an expansion of its commercial relations, which elevated Germany from a country with almost no trade relations with Iran to its largest trading partner.